Pengembangan Destinasi Wisata Melalui Pendekatan Arsitektur Kawasan di Medan Area - Lubis, Riska Damayanti; Zalukhu, Winter Jaya; Rahmadhani Fitri (Jurnal Teknik dan Teknologi Indonesia, 2024)
Medan Area sub-district can be said to be one of the sub-districts that has minimal tourist areas, seen from the identification of tourist attractions in the Medan area sub-district. Apart from that, the number of tourists arriving has decreased after the Covid-19 incident that occurred in Indonesia itself. The development of tourism in the Medan area sub-district continues to be developed to attract visitors from outside the country and outside the region to come to visit tourist areas in the Medan area sub-district. Therefor this research was conducted to analyze the needs and what kind of places will be used as tourist objects around the Medan area sub-district. As well as collecting data on an overview of the area and problems that exist in the new Medan sub-district. The final result of this research is in the form of identification of suggestions for repairs/addition of architectural objects as a result of tourism development in the area.